PENGARUH KOMPETENSI GURU EKONOMI TERHADAP PRESTASI BELAJAR SISWA SMAN 1 ARONGAN LAMBALEK KABUPATEN ACEH BARAT - Mohd Difa; Amrusi Amrusi; Sakdiyah Sakdiyah (Universitas Syiah Kuala, 2019)
Teacher competence is an interesting factor to study for two main reasons, namely (1) Teachers not only play a role in transferring knowledge to their students but provide role models for attitudes, speech, and behavior because of students. (2) Teacher professionalism is not final because as a human being, the teacher always grows and changes. Therefore teachers can improve or improve their performance in accordance with the expectations of the institution. Related to Professionalism Teachers are required to have four Competencies, namely Personality Competency, Social Competence, Professional Competence, and Pedagogical Competence. On this occasion the author will examine the Competence of Economics Teachers in SMAN 1 Arongan Lambalek. This study aims to determine (1) Competence of economics teachers at SMAN 1 Arongan Lambalek and (2) Effect of Competence on Economic Teachers on Student Achievement in SMAN 1 Arongan Lambalek. The approach used in this study is a quantitative approach to the type of descriptive research. The data source is students who represent each class of IPS XI and IPS XII using random sampling techniques. By using data collection techniques such as observation, questionnaires, and documentation. The data analysis technique used is the questionnaire validity test of questions, normality test on student achievement, and multiple linear regression using the f test and t test. Based on the results of data analysis, the findings of this study can be put forward as follows: reliability testing on the competence of economics teachers on learning achievement gets results 0.635 0.60, normality testing 0.23 0.05. Then in multiple linear regression testing, the equation Y = 73,493 + -0,28X1 + 0,294 X2 + -0,11 X3 + -0,130 X4 is obtained. In partial hypothesis testing results obtained on professional competence of -0.559, pendagogic competence of 2,311, personality competence of -0,258, and social competence of -0,890 with a table of 1,991. Simultaneous hypothesis testing obtained F test results of 1,647 with Ftable of 2.14 Then the hypothesis testing method Ho is accepted Ha rejected.